ANALYSIS OF THE IMPACT OF THE ONE VILLAGE ONE HAFIDZ PROGRAM IN IMPROVING THE QUALITY OF HUMAN RESOURCES IN WEST JAVA - Kusumawati, Riny (LPPM Univ. Ibn Khaldun Bogor, 2024)
The One Village One Hafidz program is a program that aims to motivate the community and create Hafidz in the village, in an effort to realize the Vision of West Java Juara Lahir Batin. The program is in line with the central government's vision to improve the quality of human resources, which not only emphasizes technology and education, but also religious values need to be improved. This study aims to determine the improvement of quality of human resources through the One Village One Hafidz Program in West Java and to find out inhibiting and supporting factors of the strategy of improving human resources through the One Village One Hafidz Program. The type of research used in this research is qualitative research. This research describes how the government is improving human resources through the One Village One Hafidz program in West Java. The types of data used are primary data and secondary data. Primary data was obtained through the distribution of questionnaires to research respondents. questionnaire is in the form of open and closed ended questions which are distributed through Google Form. While secondary data comes from articles or related literature. The results of data analysis showed that all the variables tested in this study had a positive and significant effect on the success of the program. The results of analysis showed that the dimensions of awareness building, meeting program needs, leaders supporting the program, setting program targets and budgets according to the scope had the largest loading factor value.